Effect of cinnamate comonomers on the dental formulation properties. Issue 4 (14th May 2012) - Buruiana, Emil C.; Jitaru, Florentina; Melinte, Violeta; Buruiana, Tinca
Abstract: This study reports the synthesis and characterization of two urethane dimethacrylates containing poly(ethylene oxide) or poly(propylene oxide) segment and cinnamate pendant moieties to be formulated in dental resin composites. 1 H NMR, 13 C NMR, and Fourier transform infrared spectroscopies, gel permeation chromatography, electrospray ionization‐mass spectroscopy, and thermogravimetric measurements confirmed their structure, whereas the photopolymerization evolution of oligodimethacrylates relating to a low–molecular‐weight dicinnamate methacrylate under ultraviolet irradiation was investigated by photo‐differential scanning calorimeter, monitoring the degree of conversion (DC) and polymerization rate. The photopolymerization results reveal that the investigated derivatives display a good photoreactivity (DC: ∼ 70%) during the formation of crosslinked polymers, the DC depending especially on the sample viscosity. The polymerization shrinkage for several mixtures including the urethane oligocinnamates (20 wt %) and diglycidyl methacrylate of bisphenol A/triethyleneglycol dimethacrylate system in the absence of filler was determined, the obtained values being in the range of 6.1–8.2 vol %. For few cured specimens incorporating quartz filler (75 wt %), water sorption/solubility, contact angle, and mechanical parameters were measured to establish if such monomers could be of interest in dentistry. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :